LOCAL PEOPLE’S PERCEPTION OF CERAMIC BEADS IN KUCHING, SARAWAK - Aina Marini, Aton; Aida Afifah, Zamhari; Shaik Azahar, Shaik Hussain (Editura Continent in cooperation with The Lucian Blaga University of Sibiu, Faculty of Economic Sciences, Center of Economic Research, 2023)
This study investigates the perception of ceramic beads among the local population, focusing on factors that increase young people's interest, affect the duration of the process, and analyze the community's perception of promoting beads using ceramic beads. The study, conducted in Kuching, reveals that the perception of residents towards ceramic beads is influenced by various factors. The findings highlight the importance of understanding community perception and offer recommendations for improvement.